Electronic tuning of misaligned coils in wireless power transfer systems - Aldhaher, Samer; Luk, Patrick Chi-Kwong; Whidborne, James F. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The misalignment and displacement of inductively coupled coils in a wireless power transfer system (WPT) can degrade the power efﬁciency and limit the amount of power that can be transferred. Coil misalignment leads the primary coil driver to operate in an untuned state which causes non-optimum switching operation and results in an increase in switching losses. This paper presents a novel method to electronically tune a Class E inverter used as a primary coil driver in an inductive WPT system to minimize the detrimental effects of misalignment between the inductively coupled coils which may occur during operation. The tuning method uses current controlled inductors (saturable reactors) and a variable switching frequency to achieve optimum switching conditions regardless of the misalignment. Mathematical analysis is performed on a Class E inverter based on an improved model of a resonant inductive link. Experimental results are presented to conﬁrm the analysis approach and the suitability of the proposed tuning method.